Stunting in Tanean Lanjhang Families in the Village of Gugul, Pamekasan District, Madura: Stunting pada Keluarga Tanean Lanjhang di Desa Gugul, Kabupaten Pamekasan, Madura - Alfina, Laily Wahyu (Universitas Airlangga, 2024)
Stunting is a condition of child growth failure with height measurement indicators caused by chronic nutritional problems. One of the traditions that still exists in Madura, especially in Pamekasan Regency, is the traditional settlement of tanean lanjhang and also the tradition of child marriage. This study was conducted to determine whether there is a significant relationship between the incidence of stunting in tanean lanjhang families. The sample of this study included children who were categorized as stunted in 5 hamlets in Gugul village, Tlanakan sub-district, Pamekasan Regency, with a total sample of 51 people with data collection techniques using interviews and measurements. Determination of informants using cluster sampling method, namely several mothers who have stunted toddlers and also the village midwife. The results showed that boys who were categorized as stunted and lived in tanean lanjhang were 11 out of 22, while girls who were categorized as stunted and lived in tanean lanjhang were 14 out of 22 children. Tanean lanjhang as a settlement tradition in Madura affects the parenting of children or grandchildren. Keywords: stunting, tanean lanjhang, child marriage. There is no significant difference between those who live in tanean lanjhang and those who do not. The daily expenditure factor is not too different because the majority of expenditures are around Rp. 50,000 / day. Then, the parenting factor affects the incidence of stunting, because of the difference between less parenting and good parenting on the incidence of stunting. There is a difference in the provision of complementary food for children between those who live in tanean lanjhang and those who do not, the provision of complementary food for children living in tanean lanjhang is mostly at the age of under 6 months, so these results can affect the incidence of stunting in children.